2015
DOI: 10.3934/genet.2015.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation control by Notch signalling during imaginal discs development in Drosophila

Abstract: The Notch signalling pathway is evolutionary conserved and participates in numerous developmental processes, including the control of cell proliferation. However, Notch signalling can promote or restrain cell division depending on the developmental context, as has been observed in human cancer where Notch can function as a tumor suppressor or an oncogene. Thus, the outcome of Notch signalling can be influenced by the cross-talk between Notch and other signalling pathways. The use of model organisms such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 145 publications
0
12
0
1
Order By: Relevance
“…Notch signalling controls cell growth and proliferation in several tissues during normal development, including imaginal discs [ 15 ] or T-cells [ 28 ], and overactivation of the Notch pathway leads to pathophysiological conditions such as wing disc hyperplasia [ 24 ] or tumour development [ 17 , 29 ]. Could Notch-dependent upregulation of metabolic genes help to stimulate tissue growth?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notch signalling controls cell growth and proliferation in several tissues during normal development, including imaginal discs [ 15 ] or T-cells [ 28 ], and overactivation of the Notch pathway leads to pathophysiological conditions such as wing disc hyperplasia [ 24 ] or tumour development [ 17 , 29 ]. Could Notch-dependent upregulation of metabolic genes help to stimulate tissue growth?…”
Section: Resultsmentioning
confidence: 99%
“…As the growth of the wing disc is dependent on Notch signalling [ 15 ] and we showed that Notch controls the expression of metabolic genes in this tissues ( figure 5 b–e ), we asked whether downregulation of metabolic genes would lead to smaller growth of the wing disc. Simultaneous downregulation of Hex-A and Impl3 or Impl3 and Glut1 using en -Gal4 driver caused significant reduction of the posterior compartment ( figure 5 h ), similar to the phenotype observed when downregulating Notch signalling [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate tissue-of-origin effects on histidine sensitivity, we compared N ACT clones in the CNS with those in the epithelium of the eye imaginal disc (Baonza & Garcia-Bellido, 2000;Brumby, 2003;Estella & Baonza, 2015). We observed that the growth of N ACT clones in the eye discs which exhibited dependency on Myc was also significantly decreased by Hdc knockdown (Fig EV4D-G).…”
Section: Histidine Deprivation Inhibits Nerfin-1 Dedifferentiation VImentioning
confidence: 98%
“…The Notch signalling pathway regulates cell proliferation and differentiation, and has been shown to function as both an oncogene or as a tumor suppressor [ 24 , 25 ]. Notch behaves as an oncogene in the Drosophila imaginal discs, in which Notch activation leads to tissue hyperplasia and tumor formation [ 26 ].…”
Section: Warburg Effect In Drosophilamentioning
confidence: 99%